The effect of acute administration of quinidine, dextromethorphan and combination of dextromethorphan/quinidine on pentylenetetrazole-induced clonic and tonic seizure thresholds in mice - Hassan Jamali; Azhdar Heydari (Fiyz̤, 2019)
Background: Dextromethorphan (DM) as a non-opioid anti-cough has neuroprotective effects. Combination of DM with quinidine decreases rapid metabolism of DM to dextrorphan (DX). This study aimed to examine the effects of acute administration of quinidine, DM and combination of dextromethorphan/quinidine (DM/Q) on pentylenetetrazole (PTZ)-induced clonic and tonic seizure thresholds in mice. Materials and Methods: A total of 84 male mice of the NMRI strain (20-25 g, n=7 in each group) were used in this study. Different doses of DM (5, 10, 25 and 50 mg/kg), quinidine (10, 20, and 30 mg/kg) and DM/Q (5/20, 10/20, 25/20, and 50/20 mg/kg) were intraperitoneally administrated 30 min before the seizure induction. Intravenous infusion of PTZ was used to induce seizure induction and latencies to the occurrence of general clonus and tonic hind limb extension were recorded and converted to the seizure threshold dose. Results: Quinidine at a dose of 30 mg/kg significantly increased the threshold of tonic seizure (P<0.05). DM at doses of 25 and 50 mg/kg significantly increased threshold of clonic (P<0.05) and tonic (P<0.001) seizures. DM/Q at dose of 50/20 mg/kg significantly decreased the threshold of clonic and tonic seizures (P<0.001). Conclusion: According to the findings of this study, different effects of DM on clonic and tonic seizure thresholds may represent different sensitivities of forebrain and hindbrain seizure circuitry to DM. Also, decreased effect of DM in the presence of quinidine may also be due to a change in the metabolism of DM.